2017
DOI: 10.1371/journal.pone.0177843
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-AF113014 promotes the expression of Egr2 by interaction with miR-20a to inhibit proliferation of hepatocellular carcinoma cells

Abstract: Long non-coding RNAs (lncRNAs), tentatively identified as non-protein coding RNA, are transcripts more than 200nt in length and accounting for 98% of the whole genome of human being. Accumulating evidence showed aberrant expressions of lncRNAs are strongly correlated to the development of cancers. In this study, AF113014 is a new lncRNA identified from Microarray. We found AF113014 is differentially expressed between HCC cell lines and normal hepatocytes. Functionally, AF113014 inhibited proliferation of HCC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Li et al showed that lncRNA n340790 accelerates cell proliferation in thyroid cancer by targeting miR-1254 [ 17 ]. Zeng et al reported that lncRNA AF113014 acts as a tumor suppressor in hepatocellular carcinoma cells by promoting Egr2 expression [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al showed that lncRNA n340790 accelerates cell proliferation in thyroid cancer by targeting miR-1254 [ 17 ]. Zeng et al reported that lncRNA AF113014 acts as a tumor suppressor in hepatocellular carcinoma cells by promoting Egr2 expression [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies found that lncRNAs could modulate the biological behaviors of HCC cells through their neighboring mRNAs [15,19]. The neighboring mRNA of CRNDE was IRX5 (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…For example, as shown in Figure 3 A , two kernels were matched to the EGR2 and ZFP64 (ZF64A) motif, respectively. EGR2 is an antitumor transcriptional factor, the induction of which could suppress the malignancy of HCC [ 34 , 35 ]. Meanwhile, the expression of ZFP64 was shown to be positively correlated to the overall survival of advanced HCC patients with the treatment of a second-line therapy [ 36 ].…”
Section: Resultsmentioning
confidence: 99%